2022
DOI: 10.1088/1755-1315/1054/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Sustainable Design Strategies for Infection Prevention and Control (IPC) in Public Buildings

Abstract: Sustainable design strategies focus on architectural design considerations which assures the welfare, in addition to cohabitation of inanimate elements, and existing creatures that constitute the ecosystem. Sustainable architecture for public spaces, in addition to energy efficiency and zero greenhouse gas emission, needs to adopt approaches that lessen the effect of communicable diseases. Often, the primarily focus of architects is the aesthetics of buildings, there is no cognizant method for sustainable infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…COVID-19 has shown that more attention should be paid to the role of indoor environments in infection prevention, especially in public buildings. Being a current topic, infection prevention in indoor environments has been approached in some recent reports discussing healthy architecture, antimicrobial surfaces, and air purification strategies (Dietz et al, 2020;Udomiaye et al, 2020;Shepley et al, 2021;Alhusban and Alhusban, 2022;Amran et al, 2022;Navaratnam et al, 2022;Tokazhanov et al, 2022;Udomiaye et al, 2022;Yong and Calautit, 2023). The articles provide useful recommendations on how to prevent the spread of infections, in particular COVID-19, through air and contact surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 has shown that more attention should be paid to the role of indoor environments in infection prevention, especially in public buildings. Being a current topic, infection prevention in indoor environments has been approached in some recent reports discussing healthy architecture, antimicrobial surfaces, and air purification strategies (Dietz et al, 2020;Udomiaye et al, 2020;Shepley et al, 2021;Alhusban and Alhusban, 2022;Amran et al, 2022;Navaratnam et al, 2022;Tokazhanov et al, 2022;Udomiaye et al, 2022;Yong and Calautit, 2023). The articles provide useful recommendations on how to prevent the spread of infections, in particular COVID-19, through air and contact surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Green building has gained much attention to achieve energy efficiency and low greenhouse gas emissions in construction (Doan et al, 2017;Udomiaye et al, 2022). However, few design and engineering-based measures have been employed to limit infection transmissions in public buildings, excluding healthcare facilities (Morawska et al, 2021).…”
Section: Open Access Edited Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Building design decisions are extremely important because they lay the foundation for a hygienic building by, for instance, affecting the movement of people several years into the future. During the design and construction phases, hygiene-related choices are made in architectural, internal facility, premise plumbing system, and HVAC design and when preparing the building's maintenance guidelines (Dietz et al, 2020;Udomiaye et al, 2020;Megahed and Ghoneim, 2021;Amran et al, 2022;Udomiaye et al, 2022). Thus, the actors involved in every stage of a building's life cycle need to be aware of how they can contribute to creating hygienic buildings.…”
Section: Implementing the Indoor Hygiene Conceptmentioning
confidence: 99%